Walk Ways - Horodner, Stuart; Portland Institute for Contemporary Art, Portland; Western Gallery - Western Washington University, Bellingham; Dalhousie Art Gallery, Dalhousie University, Halifax; Oakville Galleries, Oakville, Ontario, Oakville Galleries in Gairloch Gardens; Freedman Gallery, Albright College Center for the Arts, Reading (New York : ICI (Independent Curators International), 2002)
Alys, Francis ; Antin, Eleanor ; Antoni, Janine ; Baden, Mowry ; Campbell, Jim ; Cardiff, Janet ; Fulton, Hamish ; Harper, Sharon ; Kersels, Martin ; Marioni, Tom ; McCaslin, Matthew ; Mitchell, Curtis ; Morelli, François ; Ross, Douglas ; Spero, Nancy ; Stingel, Rudolf ; Wentworth, Richard
biog. p. 51-53
Engels
Walk Ways, Portland Institute for Contemporary Art, Portland, September 4 - November 2, 2002 ; Western Gallery - Western Washington University, Bellingham, Washington, January 6 - March 1, 2003 ; Dalhousie Art Gallery, Dalhousie University, Halifax, March 20 - May 11, 2003 ; Oakville Galleries, Oakville, Ontario, Oakville Galleries in Gairloch Gardens, June 14 - August 17, 2003 ; Oakville Galleries at Centennial Square, June 21 - August 17, 2003 ; Freedman Gallery, Albright College Center for the Arts, Reading, Pennsylvania, February 6 - March 28, 2004
boek